Multirate and multiphase switched-capacitor circuits - Dabrowski, Adam (Chapman & Hall, 1997)
This book is aimed at advanced students and researchers as well as professional design engineers. The text focuses on finite impulse response (FIR) filter structures and on infinite impulse response (IIR) SC filters which simulate classical lossless circuits . It includes coverage of the so-called pseudo-lossless SC circuits and especially multirate SC circuits with recovery of the effective pseudo-energy. There is also discussion of other promising approaches to the design of SC circuits; special attention has been paid to the analysis of multirate and multiphase SC circuits using signal flow graphs.